STUDY ON Hibiscus tiliaceus LEAVES AS ANTIBACTERIAL AND ANTIOXIDANT AGENTS - Mohamad Syahmie Samsudin; Yosie Andriani; Purbowatiningrum Ria Sarjono; Desy Fitrya Syamsumir (University of Bengkulu, 2019)
This study aimed to evaluate antioxidant and antibacterial activities of methanol, hexane, dichloromethane, ethyl acetate, and water crude sample fractions of H. tiliaceus leaves. Various type of samples play an important role to determining which compound that will give the positive results in antioxidant test (inhibiting free radical scavenging activity) which they probably have potency for preventing the cancer disease. Furthermore, those types of samples were also tested to the antibacterial test as their possibilities to be created as new antibiotics in the future. This research also focused on what compound groups that actually present in H. tiliaceus leaves by using the phytochemistry test. Antioxidant potency of H. tiliaceus leaves extracts for the radical scavenging activity for quantitative assay was measured by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. The antibacterial potency was measured by the Muller Hinton Agar (MHA) by applied the sample chemical crude in the plate. The result showed that all chemical crude of H. tiliaceus leaves has high antioxidant property as methanol crude (MC) 308.416%; hexane crude (HC) 232.837%; dichloromethane crude (DC) 150.837%; ethyl acetate crude (EC) 73.623% and water crude (WC) 71.777% with respected to the readings of 100% from quercetin (Q) as a positive control. From antibacterial result, entire samples had shown the positive results towards both gram positive (Staphylococcus aureus and Bacillus subtilis) and gram negative bacteria (Klebsiella pneumonia and Escherichia coli). The ranges of the inhibition zone were both at 7-10 mm and 10-15 mm. The phytochemistry test determine that the samples actually contained a lot of compounds which were proteins, carbohydrates, phenols/tannins, flavonoid, terpenoids, glycosides and also steroid. It is clearly indicated that H. tiliaceus leaves have potential to be used against the antioxidant and also as new antibacterial agents